Pipeline Embolization Device for Salvage Treatment of a Willis Covered Stent Prolapse Into the Aneurysmal Sac - Wu, Zeng-Bao; Wang, Sheng; Song, Li-Gang; Yang, Xin-Jian; Mu, Shi-Qing (Frontiers in Neurology, 2019)
The Willis covered stent (WCS) may prolapse into the aneurysmal sac due to device migration or foreshortening. We present a useful salvage strategy that can reorient a prolapsed WCS into a more suitable alignment. An intra-procedural prolapse of a WCS into a large cavernous aneurysm occurred in a 70-year-old female patient. A pipeline embolization device (PED) was used to retrieve the WCS and successfully accomplish flow diversion. Maintaining proximal access and ensuring that the microwire is securely held within the central axis of the herniated stent are critical until the entire parent vessel can be reconstructed. This salvage technique may help to regain proximal access and reposition the flow diversion constructs following WCS prolapse.